Implementasi Pembelajaran Fikih Berbasis Kurikulum Merdeka di Man 2 Kota Kediri - Muslih, Muhammad Ubaidillah; Riyadi, Ahmad Ali; Sholihah, Diana Nur (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to explore the implementation of Fiqh learning based on the Merdeka Curriculum at MAN 2 Kota Kediri, focusing on the planning, implementation, and evaluation aspects within the Islamic education subject. Using a qualitative method with a case study approach, this research involves in-depth interviews, participatory observations, and document analysis, including syllabi, lesson plans, and teaching materials. The findings reveal that the Merdeka Curriculum provides significant flexibility for teachers to design lessons that align with students' needs and characteristics. Teachers adopt various methods, such as Inquiry-Based Learning, Discovery Learning, and Problem-Based Learning, and utilize media and technology to enhance learning effectiveness. The integration of classical Islamic texts further strengthens students' understanding of Fiqh. The implementation process is characterized by interactive and contextual approaches, while evaluations are conducted both formatively and summatively to monitor student progress. However, key challenges include the development of teaching media and modules that meet curriculum standards. Regular supervision by the school principal serves as an effort to support innovation and improve teaching quality. This research concludes that the Merdeka Curriculum positively contributes to Fiqh learning in madrasahs and offers practical recommendations for improving the quality of Islamic education, particularly within the context of a modern curriculum framework.